2011
DOI: 10.1007/s10950-011-9262-7
|View full text |Cite
|
Sign up to set email alerts
|

Locating the Tohoku-Oki 2011 tsunami source using acoustic–gravity waves

Abstract: The giant Tohoku-Oki earthquake of 11 March 2011 in offshore Japan did not only generate tsunami waves in the ocean but also infrasound (or acoustic-gravity) waves in the atmosphere. We identified ultra-long-period signals (>500 s) in the recordings of infrasound stations in northeast Asia, the northwest Pacific, and Alaska. Their source was found close to the earthquake epicenter. Therefore, we conclude that in general, infrasound observations after a large offshore earthquake are evidence that the surface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…So far, observation of the Tohoku neutral waves has been limited to the detection of gravito‐acoustic waves with micro‐barometers [ Arai et al , ; Raveloson et al , ]. We present here the first direct observation of post‐seismic neutral acoustic waves in the thermosphere, along the GOCE orbit.…”
Section: Introductionmentioning
confidence: 88%
“…So far, observation of the Tohoku neutral waves has been limited to the detection of gravito‐acoustic waves with micro‐barometers [ Arai et al , ; Raveloson et al , ]. We present here the first direct observation of post‐seismic neutral acoustic waves in the thermosphere, along the GOCE orbit.…”
Section: Introductionmentioning
confidence: 88%
“…[9] The Earth's surface is a speaker [Rayleigh, 1945]. Seismic shaking of the surface generates sound spanning the audible and infrasonic frequency ranges.…”
Section: Radiation Of Infrasound From Surface Shakingmentioning
confidence: 99%
“…Areas of high-frequency seismic radiation occurred near the western edges of the rupture plane closest to Sendai [Simons et al, 2011]. Several studies have found evidence for long-period infrasound or gravity waves generated from uplift in the source region [Arai et al, 2011;Nishitani et al, 2011;Chum et al, 2012;Raveloson et al, 2012;Garcia et al, 2013].…”
Section: Tohoku Earthquakementioning
confidence: 99%